CONTROVERSIES AND TRANSITIONS FOR SUSTAINABLE DEVELOPMENT - Théry, Neli de Mello; Caron, Patrick (Mercator, 2020)
Science does not progress without controversy as well the societies. In this article, this approach is privileged, aiming to analyze whether they can hinder or speed up the agricultural and food, environmental and sanitary transitions necessary to achieve the Sustainable Development Goals (SDGs). It begins with an alert to the past development model and the limits of the planet, highlighting some themes and forms of action chosen by international institutions and / or scientist’s networks. Then, we selected some controversies and their arguments, related to environmental issues and the evolution of food systems. In the subsequent item, its actors and five sub controversies sought to highlight the difficulties for the transition to circular systems, considered as a vector of sustainability. It is concluded that controversies can block advances for transitions, being essential the design of methods, criteria and indicators for a better understanding of oppositions, as well as the need to include both themes and new approaches in research agendas.